Can persuasive normative messages encourage sustainable transportation usage?. (November 2021) - Piras, Francesco; Manca, Sara; Sottile, Eleonora; Meloni, Italo; Mosca, Oriana; Tuveri, Giovanni; Fornara, Ferdinando
Highlights: We explore the effect of the delivery of a normative message on travel behavior. The difference between injunctive and descriptive norm is investigate. An experimental study was conducted among a sample of 340 individuals. Individuals who receive an injunctive norm are more likely to use sustainable transport. Abstract: One way to persuade people to change their travel behaviours is to execute strategies based on the provision of persuasive normative messages. Several studies have reported that providing information on social norms can lead people to perform different pro-environmental actions, such as energy and water conservation. However, in the transportation field, little research has investigated whether normative messages can be used to encourage people to switch from driving cars to using more sustainable means of transport. The aim of the current paper is to explore whether the intention to use different travel modes can be influenced by a persuasive normative message. In particular, we studied the different impacts of descriptive norm and injunctive norm information alongside more traditional factors on the intention to use a car, public transport, or active mobility. To perform our analysis, we developed three integrated choice and latent variables (ICLV) models using the information collected from an experimental study conducted among a sample of 340 individuals living in the area of Cagliari (Sardinia, Italy). One of our modelling results indicates that individuals are more likely to use sustainable means of transport if they i) have previously used such means, ii) have a positive attitude toward them, iii) have an interest/involvement in using them, and iv) have been exposed to injunctive norms related to their use. Importantly, the computation of the pseudo-elasticity effect revealed that the impact of past behaviour is much stronger than the impact of normative messages.